Implementasi Disiplin Positif Pada Mata Pembelajaran Pendidikan Agama Islam Di SD Negeri 05 Kabawetan - Vebriani Dewinita; Idi Warsah (GHAITSA : Islamic Education Journal, 2025)
Religion is the main foundation in life because religion is a basic teaching for the life of Muslims, the main teaching for humans is morals and piety. One of the aims of religious education is to instill piety and good morals and uphold the truth in order to realize a human being with personality and character in accordance with Islamic teachings. The purpose of this study is how the role of Islamic Religious Education teachers is in shaping the morals of students at SD Negeri 03 Kabawetan. The research method used in this study is qualitative. Data collection techniques in this study are observation, interviews and documentation. From the results of this study, namely, the role of Islamic Religious Education teachers greatly helps the morals of students at SD Negeri 03 Kabawetan to become polite, well-behaved, wise and civilized students.